The Effect Of Healthy Snacks Education On Students' Knowledge - Usi Lanita (Lembaga Pengembangan Kinerja Dosen, 2024)
Elementary school children are a group vulnerable to food poisoning caused by unhealthy snacks containing dangerous substances such as formaldehyde, borax, rhodamine, and methanol yellow. The aim of the research is to determine the effect of healthy snack education on students' knowledge. This type of research is quasi-experimental, with a sample of 30 students and data analysis using the Wilcoxon test. The result was an increase in knowledge, as seen from the pre-test and post-test results. There was a significant increase in knowledge (p-value < 0.001). It can be concluded that there is an influence of healthy snack education on elementary school students' knowledge. It is hoped that the school will support it by providing healthy canteens in elementary schools.